Direct and indirect top-down effects of previous contact with an enemy on the feeding behavior of blowfly larvae - Reigada, Carolina [UNESP]; Godoy, Wesley A. C. (Wiley-Blackwell, 2012)
We investigated the addition of a trophic level to a simple food web. Direct and indirect effects caused by the presence of a new species in the food web were quantified by estimating survival and consumption rates on the basal resource. We focused on a blowfly intraguild preypredator system with various ecological interactions taking place during the larval period. The experiments were designed to set Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) as the intraguild prey and Chrysomya albiceps (Wiedemann) as the intraguild predator and/or cannibal. The generalist pupal parasitoid Nasonia vitripennis (Walker) (Hymenoptera: Pteromalidae) was introduced into the system during a non-susceptible life stage of the interacting blowfly species. The cascading parasitoid effects induced behavioral changes in the blowfly larvae, increasing the impact of intraguild predation and cannibalism on blowfly survival. The results suggest that blowfly larvae can change their feeding behavior in response to the presence of a parasitoid.
Keywords: intraguild predation; cannibalism; interaction effects; Chrysomya megacephala; Chrysomya albiceps; Nasonia vitripennis; Diptera; Hymenoptera; Pteromalidae; Calliphoridae